KONTRIBUSI PENDAPATAN AGROWISATA PADI SAWAH TERHADAP PENDAPATAN RUMAH TANGGA PADA BERBAGAI KATEGORI DESA WISATA - handayani, sugiharti mulya; Jamhari, Jamhari; Waluyati, Lestari Rahayu; Mulyo, Jangkung Handoyo (AGRARIS: Journal of Agribusiness and Rural Development Research, 2019)
Tourist village as a new trend of tourism that has been growing rapidly in Yogyakarta. Based on attractiveness, accessibility, facilities, community empowerment, marketing and promotion, institutional, and human resources, tourist villages are devided into growing, developing and developed categories. Wetland rice agrotourism offers attractions in tourist village that leads to increasing income of the perpetrators (main actors, supporting actors, and managers). This descriptive research aimed to compare agro-tourism perpetratorsâ€™s income contribution to household income in various categories of tourist village in Yogyakarta. This research was purposively conducted in Gabugan, Pancoh and Pentingsari Village as representation of grow, developed, and advanced tourism villages. The result depicted that the contribution of wetland rice agrotourism to household income of all agro-tourism actors was low in all tourism village categories. This indicates that the wetland rice agro-tourism has not contributed significantly in supporting the domestic economy of the perpetrators.Â The results of the study show that the advanced tourism villages have a higher contribution of income compared to developing and growing tourism villages.